Adaptation of The Creative Economy: Consumer Perception On Digital Transformation of Culinary SMEs In Langsa City - Lubis, Nasrul Kahfi; Rosalina, Dhian; Zati, Muhammad Rizqi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Digitalization is a must to maintain business consistency In the era of pandemics and technological advance. The culinary sector in Langsa City continues to grow, with a wide market ranging from students, students, and households, to industry causing several culinary destinations such as traditional and modern cafes to gain public interest. This study aims to analyze 1) How to adapt the digital transformation of SMEs in the culinary sub-sector in Langsa City, and 2) How is the creativity of the culinary sub-sector actors in the digital transformation adaptation period. This research method was descriptive and quantitative. The respondents of this research are one hundred people who are culinary consumers of Langsa city. Two aspects were measured in the research: digital transformation and innovation carried out by culinary SMEs. The results show that the Culinary SMEs in Langsa City has adapted to digital transformation in their business well. Culinary SMEs show that they have been innovating and being creative in the products offered. Product innovations ranging from taste, packaging, size, and so on are considered quite good and competitive, this shows that SMEs can adapt to compete in the culinary subsector.